The Influence of the Project Based Learning Model on Student Learning Outcomes in History Subject of Class X E At SMA Negeri 1 - Hijratul; Hasan; Idrus A rore; Ismail (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research was motivated by the decline in students' learning outcomes in class X E, as evidenced by the average score of 31.88 in the odd semester examination of the 2024/2025 academic year for the History subject, as well as the use of conventional teaching methods which are considered boring. The aim of this study was to determine the influence of the Project Based Learning model on students' learning outcomes in class X E. The method used in this research was a Quasi-experimental design with a non-equivalent control group, involving an experimental class (X E) and a control class (X F) with purposive sampling techniques, and the research sample consisted of 29 students. The results of the Mann Whitney U analysis showed an Asymp. Sig. (2-tailed) value of 0.017 < 0.05, thus the alternative hypothesis (H₁) was accepted and the null hypothesis (H₀) was rejected. Therefore, there is a significant influence of the Project Based Learning model on students' learning outcomes in the History subject in class X E At SMA Negeri 1 Sigi.